Modeling of Land-Use and Ecological Dynamics - Malkinson, Dan.; Czamanski, Danny.; Benenson, Itzhak. (Cities and Nature, 2013)
As cities are rapidly expanding and encroaching into agricultural and natural areas, a question of primary concern is how this expansion affects surrounding agriculture and natural landscapes. This book presents a wide spectrum of both theoretical and empirical approaches to simulation and assessment of landscape dynamics. The first part presents state-of-the-art modelling approaches pertaining to land-use changes entailed by the urban sprawl, at different spatial resolutions and temporal time scales. The second part is dedicated to case studies of the effects and consequences of the emerging urban-agriculture open space patterns.